Схожість та відмінність популяції гемопоетичних стовбурових/ прогеніторних клітин із різних тканин людини - Кучма, М.Д.; Кирик, В.М.; Світіна, Г.М.; Шаблій, Ю.М.; Лукаш, Л.Л.; Лобинцева, Г.С.; Шаблій, В.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. We have determined the similarities and the differences of HSPCs populations from the full-term placental tissue (FTPT) compared to HSPCs from the cord blood (CB) and the fetal liver (FL). Methods. HSPCs from FTPT have been obtained by enzymatic method. The immunophenotyping have been performed on BD FACSAria (USA). MethoCult (Canada) has been used for differentiation assays. Results. The content of HSPCs (CD34⁺ CD45^lowSSC^low) among CD34⁺ CD45^low population from FTPT and FL was the same but significantly lower comparing to CB. FTPT contains significantly higher number of lineage committed HSPCs in compare to CB but lower than to FL. HSPCs from FTPT and CB have similar potential to multilineage differentiation in vitro. Conclusions. Observed similarities and differences of HSPCs from studied tissues and other data evidence about the process of placental hematopoiesis and permit to suggest that FTPT is a valued source of HSCs for medicine.